Children’s perspectives on being absorbed when reading fiction: A Q methodology study - Kuzmičová, Anežka; Supa, Markéta; Nekola, Martin (Frontiers in Psychology, 2022)
Research in the intersections of literature, media, and psychology increasingly examines the absorbing story experiences of adult readers, typically relying on quantitative self-report questionnaires. Meanwhile, little work has been done to explore how being “lost in a book” is experienced by children, despite the phenomenon’s importance for literacy education. Such work requires tools that are more inductive and child-centered than questionnaires. We have conducted a Q methodology study with participants aged 9-12 (n = 28), exploring how it feels for them when the mind and body are attuned to a story and how different facets of absorption (e.g., mental imagery, emotional engagement) inform the experience. Participants numerically sorted 24 cards expressing inner states and expectations relating to book-length fiction reading and were subsequently interviewed regarding their sorting choices. The cards were generated inductively based on preliminary research (focus groups, individual interviews, observations). By-person factor analysis of the sortings combined with reflective thematic analysis of the post-sorting interviews revealed four distinct reader subjectivities, or perspectives: Growth, Confirmation, Attachment and Mental Shift. Crucially, the children in these groups differed as to prominent dimensions of absorption but also as to the overall place of reading in their inner and everyday lives. Based on the four perspectives, we demonstrate that children have varied ways of being absorbed when reading fiction, and reflect on the affordances of Q methodology as a suitable child-centered approach to studying the subjective experiences of reading.